SISTEM PENDUKUNG KEPUTUSAN PENENTUAN JUMLAH PRODUKSI PADA ZUHRO BAKERY MENGGUNAKAN METODE WEIGHTED PRODUCT - Risma, Haliza; Sulindawaty, Sulindawaty (STMIK Kaputama, 2020)
The amount of production is very influential on a Zuhro Bakery home industry, without the amount of production how a Zuhro Bakery home industry has increased if it does not have a regulation on the amount of bread production. In making decisions 1 to determine the amount of production, especially in the business sector contains risks. In the field of business needs to be supported by careful calculation so that the risk of loss can be avoided. Zuhro Bakery's home industry still determines the amount of production manually. From the above problems, a decision support system (SPK) was made using the weighted product method. Based on the calculation using the Weighted Product method for the Total Production at Zuhro Bakery, the largest value is V1, V2, V3, V4, V5 so that alternatives A1, A2, A3, A4, A5 are the alternatives chosen as the best alternative. Namely chocolate, donuts, chicken thighs, green beans, peanuts will be increased even more the amount of production.